Influence of Electron Acceptor and Electron Donor on the Photophysical Properties of Carbon Dots: A Comparative Investigation at the Bulk‐State and Single‐Particle Level. (4th July 2019) - Srivastava, Indrajit; Khamo, John S.; Pandit, Subhendu; Fathi, Parinaz; Huang, Xuedong; Cao, Anleen; Haasch, Richard T.; Nie, Shuming; Zhang, Kai; Pan, Dipanjan
Abstract: Carbon dots (CDs) are extensively studied to investigate their unique optical properties such as undergoing electron transfer in different scenarios. This work presents an in‐depth investigation to study the ensemble‐averaged state/bulk state and single‐particle level photophysical properties of CDs that are passivated with electron‐accepting (CD‐A) and electron‐donating molecules (CD‐D) on their surface. The bulk‐state experiments reveal that in a mixture of these CDs, CD‐A dominates the overall photophyiscal properties and eventually leads to formation of at least two associated geometries, which is dependent on time, concentration, intramolecular electron/charge transfer, and hydrogen bonding. Single‐particle studies, however, do not reveal an "acceptor‐dominating" scenario based on analysis of instantaneous intensity, bleaching kinetics, and photoblinking, indicating that the direct interaction of these CDs may affect their photophysical properties in the bulk state due to formation of hierarchical structural assemblies. Here it is anticipated that these fundamental results will further provide insights toward the understanding of the complex mechanism associated with CD emission, which is one of the key contributors to their successful application. As an immediate application of these functional CDs, it is shown that they can be used as a sensing array for metal ions and serve as a powerful toolbox for their technological applications. Abstract : Photophysical properties of carbon dots (CDs) passivated with electron‐accepting (CD‐A) and electron‐donating molecules (CD‐D) on their surface are studied extensively at both the bulk‐state and single‐particle level. The work reveals that upon mixing, CD‐A dominates the photophysical properties and leads to at least two associated geometries. This study is beneficial for tuning the optoelectronic properties of CDs towards a specific goal.